2020
DOI: 10.1007/s00220-020-03857-3
|View full text |Cite
|
Sign up to set email alerts
|

A Non-degenerate Scattering Theory for the Wave Equation on Extremal Reissner–Nordström

Abstract: It is known that sub-extremal black hole backgrounds do not admit a (bijective) non-degenerate scattering theory in the exterior region due to the fact that the redshift effect at the event horizon acts as an unstable blueshift mechanism in the backwards direction in time. In the extremal case, however, the redshift effect degenerates and hence yields a much milder blueshift effect when viewed in the backwards direction. In this paper, we construct a definitive (bijective) non-degenerate scattering theory for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…When |e| = M, the mode solutions corresponding to any homogeneous solution to the ODE are smooth at the horizon and at infinity with respect to 1/r , which is consistent with the scattering theory viewpoint in[8] where exponentially decaying data along future null infinity and the event horizon that lead to smooth solutions can be chosen independently.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…When |e| = M, the mode solutions corresponding to any homogeneous solution to the ODE are smooth at the horizon and at infinity with respect to 1/r , which is consistent with the scattering theory viewpoint in[8] where exponentially decaying data along future null infinity and the event horizon that lead to smooth solutions can be chosen independently.…”
supporting
confidence: 78%
“…See also [6] for an illustration of the importance of conserved quantities along future null infinity in the sub-extremal setting. [8], a scattering theory is developed in extremal Reissner-Nordström involving non-degenerate energies. As an application of this theory, it is shown that for any smooth, superpolynomially decaying scattering data along the event horizon and future null infinity, there exists a corresponding unique solution to (1.2) that is smooth along an asymptotically null foliation and is moreover smooth with respect to the coordinate 1 r at r = ∞.…”
Section: Uniform Decay Estimatesmentioning
confidence: 99%
See 3 more Smart Citations